Potentials of Sweet Potato (Ipomoea batatas) Leaf Meal as Dietary Ingredient for Tilapia zilli Fingerlings - Adewolu, M.A. (Pakistan Journal of Nutrition, 2008)
An 8-week feeding trial was conducted to evaluate the potential of sweet potato (Ipomoea batatas) leaf meal as dietary protein source in the diet of Tilapia zilli fingerlings. Five isonitrogenous diets of 30% crude protein were formulated to contain 0, 5, 10, 15 and 20% sweet potato leaf meal (Diets 1-5) to partially replace other protein ingredients in the tilapia diet. The diet containing 0% leaf meal served as the control. Tilapia zilli fingerlings were reared in 50L circular plastic tanks maintained in a flow-through system. Each dietary treatment was tested in triplicate groups of 10 fingerlings per tank. The results of the growth and nutrient utilization responses show that there were no significant (p>0.05) differences among the fish fed diets 1-4 (0-15% sweet potato leaf meal) but were significantly (p0.05) differences in the carcass composition of Tilapia zilli fingerlings fed on experimental diets. The present findings show that sweet potato leaf meal has good potential for use as one of the protein sources in Tilapia zilli diet up to 15% level without compromising growth.